Comparison of machining performance under MQL and ultra-high voltage EMQL conditions based on tribological properties. (January 2021) - Shah, Prassan; Gadkari, Ameya; Sharma, Akash; Shokrani, Alborz; Khanna, Navneet
Abstract: This novel work presents the comparison of a newly developed ultra-high voltage electrostatic minimum quantity lubrication (EMQL) using a customized nozzle with the MQL technique as an alternative cooling/lubricating method in turning processes of 15–5 PHSS. The optimum voltage for EMQL within the range of 0–25 kV has been identified based on tribological performance. Besides, surface roughness has been measured to identify the impact of electrostatically charged mist for turning 15-5 PHSS. Finally, tool wear tests are performed for MQL and EMQL at optimized voltage. The EMQL at optimized electrostatic voltage resulted in 38% decreased tool wear as compared to conventional MQL for 2400 mm cutting length. Highlights: A novel Electrostatic Minimum Quantity Lubrication (EMQL) setup is compared with MQL at various electrostatic voltage. Electrostatic voltage is optimized based on results of droplet quality, tribological properties and surface roughness. EMQL at optimized electrostatic voltage resulted in 38% decreased tool wear as compared to conventional MQL.